Effect of Organic and Inorganic Nanoparticles on Colour Stability and Mechanical Properties of Heat Vulcanised Maxillofacial Silicone Elastomer: a Comparative Study - Manisha Khanna; Komal Sehgal; Shefali Singla; Virender Kumar (Stilus Optimus, 2024)
Objectives: The purpose of this comparative study in vitro was to evaluate the effect of organic and inorganic nanoparticles on colour stability, tear strength and hardness of maxillofacial silicone elastomer at baseline and when subjected to outdoor weathering for 6 months. Material and Methods: A total of 240 specimens were fabricated using M511 platinum silicone which were divided into total 4 groups (n = 60) based on the type of nanoparticles (control, polytetrafuoroethylene [PTFE], titanium dioxide [TiO2], zinc oxide [ZnO]) added and each group was further divided into 3 subgroups (n = 20) for colour, tear strength (TS) and hardness (H) testing. The tests were conducted and data was obtained both before and after outdoor weathering of 6 months. Results: Minimum colour change after weathering was observed in PTFE group (∆E = 2.23). TiO2 group showed maximum TS (12.01 N/mm) followed by PTFE group (10.85 N/mm) before weathering. After weathering, maximum TS was shown by TiO2 group (12.9 N/mm) and PTFE group (12.54 N/mm). TiO2 group showed maximum hardness (24.15 shore A) before weathering and PTFE group showed maximum hardness (33.43 shore A) after weathering. Conclusions: Within the limitations of this study, it can be concluded that the addition of polytetrafuoroethylene nanoparticles to the polymer enhances both the optical as well as mechanical properties and can be considered favourable for the extended life of the prosthesis.